Técnica de sentadilla y su incidencia en el rendimiento deportivo de la selección femenina de levantamiento de potencia de la federación deportiva de los Ríos - Vargas Lucio, Diana Carolina (2016)
This research was conducted at the Sports Federation Rivers, by developing this work the way it influences the technique squat in athletic performance of the women's Powerlifting was studied, whose objective was to determine the incidence have these variables, for this the technical implementation was evaluated, the individual and collective sports performance was also analyzed through the review of the results of the competitions, it was found that in recent years the women's team is not among the top podium places and even not recorded consecutive competitions in the national archives due to its low sports performance descriptive research was used, techniques of observation and surveys. According to the results of the investigation it showed that most lifters have problems with body posture and grip the bar preventing properly execute the various types of squat practiced in powerlifting, therefore coaches recommended use audiovisual media in gyms to impart their knowledge, and establish timetables for discussions after several days of training, allowing reflection of athletes and giving space to express their views regarding your training, be aware of their shortcomings and strengths for the continuous improvement of their daily practices. As proposed application arises to design a methodological guide squat flipped classroom approach to help athletes improve performance art